Clinical researchAdvantage of adjunct metformin and insulin therapy in the management of glycemia in critically ill patients. Evidence for nonoccurrence of lactic acidosis and needing to parenteral metformin - Mojtahedzadeh, Mojtaba; Rouini, Mohammad R.; Kajbaf, Farshad; Najafi, Atabak; Ansari, Ghazal; Gholipour, Afshin; Mofid, Ali R.; Abdollahi, Mohammad (Archives of Medical Science, 2008)
Introduction: Stress-induced hyperglycemia is associated with insulin resistance in critically ill patients. In order to overcome insulin resistance, clinicians increase insulin dose that could result in hypoglycemia, hypokalemia, hypomagnesemia, and other complications. Material and methods: This randomized clinical study was conducted among thirty-three traumatized adult patients who were admitted to medical-surgical ICU of a reference University hospital. Patients were randomly assigned to receive one of three protocols including intensive insulin monotherapy (A), metformin monotherapy (B), and intensive insulin therapy in combination with metformin (C) to maintain blood glucose level between 80-120 mg/dl. For pharmacokinetic study of metformin a validated ion pair HPLC method was also applied. Results: Three protocols A, B, and C successfully reduced admission blood glucose levels from 191±28, 189±35, and 192±28 mg/dl to 122±9, 131±17, and 121±7 mg/dl (mean ± SD), as mean weekly values, respectively. These reductions were significant in protocols A (P=0.02) and B (P=0.003). Protocol C showed 34% reduction in mean weekly insulin requirements as compared with protocol A. Although patients in protocols B and C had some fluctuations in their blood lactate levels, lactic acidosis did not occur in any patient. Pharmacokinetic data showed a deficit in oral absorption of metformin in critically ill patients. No direct relationship was observed between pharmacokinetic and pharmacodynamic profile of metformin during the course of critical illness. Conclusions: It is concluded that metformin reduces insulin requirements in glycemic management of critically ill patients independent of its plasma concentration. Metformin seems to be effective to reverses insulin resistance without induction of lactic acidosis.